WARNA LOKAL BALI DALAM NOVEL DI BAWAH LANGIT YANG SAMA KARYA HELGA RIF - Selvi Rita Sari; Christanto Syam; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe research focused to analyze Bali’s local colour in the novel Di Bawah Langit yang Sama by Helga Rif. Researcher focused on the local colour because it was dominate in the novel. This research aimed to describe about life habits, attitudes and the implementation plan of research results to literary learning. Researcher use qualitative research method and describtive research form with literary sociology study. Data source of this research is novel Di Bawah Langit yang Sama. Data of this research were the occurrences of quotation in the text. Technique in data collection is documentary study. Data collection tools is researcher as main instrument and assisted with registrar tools. The result of this research were life habits in Ngaben ceremony divided to the  type of  Ngaben, stages, tools and the restrictions. Life habits in marriage ceremony divided on the system of  marriage, stages, marriage procession ceremony, and tools. The third life habits were in Maturan. The result about attitudes were tolerance for foreign cultures, surrender to God, assertive, courageous, obedient, responsibilities, respect and mutual help, keep others feeling, friendly, wise, politeness, patience and sincere. The researcher was planning about literary implementation learning use narrative text based on Basic Competencies and syllabus.   Keywords: Attitudes, Life Habits, Local Colour,  Novel.